2017
DOI: 10.1038/s41598-017-04238-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular methods to detect Spodoptera frugiperda in Ghana, and implications for monitoring the spread of invasive species in developing countries

Abstract: Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) is a polyphagous pest indigenous throughout the Americas, which recently appeared in Africa, first reported from São Tomé, Nigeria, Bénin and Togo in 2016, and which we now report from Ghana. This species is recognised to comprise two morphologically identical but genetically distinct strains or species in the Americas, and we found both to be present in Ghana. We discuss possible routes of entry to Africa, of which the likeliest is adults and/or egg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
205
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(214 citation statements)
references
References 31 publications
3
205
0
6
Order By: Relevance
“…This invasive pest was first reported in West Africa in late 2016 (Goergen, Kumar, Sankung, Togola, & Tamo, ); by early 2017, the pest invaded Sub‐Saharan Africa. Recent reports confirmed the occurrence of fall armyworm in 28 countries in Africa (Cock, Beseh, Buddie, Cafa, & Crozier, ; Day et al., ) indicating the rapid spread of the pest in the African continent, threatening the food security of millions of people. Recent studies conducted by Centre for Agriculture and Biosciences International in 12 maize‐producing countries showed that, without control, fall armyworm can cause maize yield losses ranging from 8.3 m to 20.6 m tonnes per year (Day et al., ).…”
Section: Introductionmentioning
confidence: 82%
“…This invasive pest was first reported in West Africa in late 2016 (Goergen, Kumar, Sankung, Togola, & Tamo, ); by early 2017, the pest invaded Sub‐Saharan Africa. Recent reports confirmed the occurrence of fall armyworm in 28 countries in Africa (Cock, Beseh, Buddie, Cafa, & Crozier, ; Day et al., ) indicating the rapid spread of the pest in the African continent, threatening the food security of millions of people. Recent studies conducted by Centre for Agriculture and Biosciences International in 12 maize‐producing countries showed that, without control, fall armyworm can cause maize yield losses ranging from 8.3 m to 20.6 m tonnes per year (Day et al., ).…”
Section: Introductionmentioning
confidence: 82%
“…The rapid spread and establishment of H. armigera across much of the South American continent has generated a very large population with significant impacts on agricultural production. In contrast to usual invasions such as the African incursion of the New World fall armyworm S. frugiperda [16,34,[39][40][41][42], the invasive H. armigera population in the New World appears to be very diverse. Furthermore, the spatial distribution of this diversity strongly suggests that the population has spread from two different regions of introduction.…”
Section: Discussionmentioning
confidence: 97%
“…Further studies are also warranted to assess the performance of C. icipe on S. exempta and S. frugiperda. The African armyworm S. exempta is a serious pest of maize and rice, the most important staple crops across Africa (Grzywacz et al 2008, Okello-Ekochu and Wilkins 1996, Sithole 1989) while the fall armyworm S. frugiperda is a newly reported invasive pest on the continent, causing currently the highest damage on maize, rice, sorghum and millet (Cock et al 2017, Goergen et al 2016. Cotesia icipe represents therefore a potential candidate for natural control of pests of these staple crops.…”
Section: Discussionmentioning
confidence: 99%